(untitled) (Eurasian Medical Research Periodical, 2026)
This study investigated the diagnostic and prognostic significance of immunological panels and non-invasive biochemical indices in predicting the development of autoimmune hepatitis (AIH) in patients with autoimmune hemolytic anemia (AIHA). The prognostic potential of Liver-9-Line immunological systems, as well as APRI, FIB-4, King’s score, and the De Ritis index, was evaluated at the early and late stages of the disease. The analysis demonstrated that immunological panels possess higher diagnostic and prognostic efficiency compared to conventional indices. In particular, Liver-9-Line and Liver-3-Line were identified as the most reliable markers for the early detection of AIH development. The obtained results confirm that immunological profiling plays an important role in the early identification and monitoring of patients belonging to highrisk groups.